The Soviet Feldsher as a Physician's Assistant - United States. Public Health Service; National Institutes of Health (U.S.); United States. Department of Health, Education, and Welfare (US Department of Health, Education, and Welfare, 1972)
This monograph published in 1972 by the Department of Health, Education and Welfare (DHEW) was written by Patrick B. Storey, MD as part of a series of studies on medicine and public health in the Soviet Union conducted in the summer of 1970. The studies were performed by the John E. Fogarty International Center for Advanced Study in the Health Sciences, National Institutes of Health (NIH). The duties and education of feldshers are described and the historic and geographic determinates for their use are discussed. The author concludes that "the concept of physician associates as we are presently developing the idea in the United States does not have a direct precedent in the Soviet Union. The resemblance is more remote."